PENGARUH MODIFIKASI LATIHAN DOUBLE LEG BOX BOUND TERHADAP EXPLOSIVE POWER OTOT TUNGKAI PADA SISWA KELAS X SMA 12 PEKANBARU - Zulya, Arlan; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on observations on a badminton player class X SMA 12 Pekanbaru, researchers found that the phenomenon of leg muscle explosive power in badminton player class X SMA 12 Pekanbaru still looks less than the maximum. The purpose of this research was to determine whether there are significant modifications to practice double-leg box bound to the explosive power leg muscle in Class X SMA 12 Pekanbaru. This study was an experimental study. In this study the authors took samples from the majority population in 12 high school students of class X MIPA Pekanbaru 4 male students as many as 14 people. The instrument of this study tests used are standing Broad Jump.Data tests analyzed using normality test and test hypotheses. Furthermore, to determine the extent of the Effect of Modification Exercises Double Leg Box Bound Against Explosive Power Muscles Legs In Class X SMA 12 Pekanbaru seen from t = 3,756, while table = 1,771 and this means that there Effect of Modification Exercises Double Leg Box Bound Against Explosive Power Limbs muscles In Class X SMA 12 Pekanbaru or Ho rejected and Ha accepted. Then, the results showed a significant difference to the upgrading of 12:09%. Keywords: Modified Double Leg Exercises Box Bound, Muscle Power Explosive Limbs